2020
DOI: 10.1111/ggi.13885
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition risk and hospital‐acquired falls in older adults: A cross‐sectional, multicenter study

Abstract: Aim To assess the relationship of malnutrition risk and in‐hospital falls in a patient group of older hospitalized patients (65–79 and ≥80 years). Methods A cross‐sectional, multicenter, point‐prevalence study was conducted in 68 Austrian hospitals with 3702 hospitalized older patients. The relationship between malnutrition risk and falls was analyzed using univariate and multivariate binary logistic regression analyses. Data were analyzed separately for two age groups, patients were aged 65–79 years (n = 2320… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…The timing of diagnoses, length of hospital stay, and comorbidities might have influenced Lackoff et al's study results. Eglseer et al reported that in a multivariate analysis, in-hospital falls in older patients were not significantly associated with malnutrition [27]. However, their study examined in-hospital falls before assessing malnutrition.…”
Section: Discussionmentioning
confidence: 96%
“…The timing of diagnoses, length of hospital stay, and comorbidities might have influenced Lackoff et al's study results. Eglseer et al reported that in a multivariate analysis, in-hospital falls in older patients were not significantly associated with malnutrition [27]. However, their study examined in-hospital falls before assessing malnutrition.…”
Section: Discussionmentioning
confidence: 96%
“…Malnourished old patients are at a higher risk of falls in hospitals when compared with those with preserved nutritional status. In particular, the risk of falls increases up to 8.4% and 6.2% in geriatric and internal medicine wards, respectively, and the global fall rate rises up to 31.6% up to 39.5% in patients ≥80 years [65]. Old patients with malnutrition and independent activities of daily living (ADL) were recently reported with a 2.7 higher risk of in-hospital falls [66].…”
Section: Malnutrition Falls and Other Complications Of Hospitalizationmentioning
confidence: 99%
“…In einer Erhebung in Österreich bei Patient*innen über 65 Jahren liegt der Anteil von Patient*innen mit einem Mangelernährungsrisiko laut Screening bei 24,3 %. Dieses ist mit einem erhöhten Sturzrisiko in der Klinik assoziiert [3]. In einer britischen Erhebung bei zu Hause lebenden Senioren weisen 44,2 % ein hohes und 25,2 % ein mittleres Mangelernährungsrisiko auf [4], was für ein generell erhöhtes Risiko bei älteren Menschen spricht, auch abseits akuter und schwerer Erkrankungen.…”
Section: Introductionunclassified